The neural basis of the speed-accuracy tradeoff. - Bogacz, R; Wagenmakers, E; Forstmann, B; Nieuwenhuis, S (2010)
In many situations, decision makers need to negotiate between the competing demands of response speed and response accuracy, a dilemma generally known as the speed-accuracy tradeoff (SAT). Despite the ubiquity of SAT, the question of how neural decision circuits implement SAT has received little attention up until a year ago. We review recent studies that show SAT is modulated in association and pre-motor areas rather than in sensory or primary motor areas. Furthermore, the studies suggest that emphasis on response speed increases the baseline firing rate of cortical integrator neurons. We also review current theories on how and where in the brain the SAT is controlled, and we end by proposing research directions that could distinguish between these theories.